2022
DOI: 10.1145/3512956
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Diversity in Electronic Music: the Impact of Listener, Artist, and Track Characteristics

Abstract: Shared practices to assess the diversity of retrieval system results are still debated in the Information Retrieval community, partly because of the challenges of determining what diversity means in specific scenarios, and of understanding how diversity is perceived by end-users. The field of Music Information Retrieval is not exempt from this issue. Even if fields such as Musicology or Sociology of Music have a long tradition in questioning the representation and the impact of diversity in cultural environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Particularly, the proposed HC and MIX methods appear to significantly outperform the random baseline for SGD and XGB models. This finding leads us to promote the creation of subjectivity-aware machine learning methods which could have a high impact in novel applications of immersion in virtual reality (Warp et al, 2022) and emotion-based music recommendation (Grekow, 2021;Tarnowska, 2021)-several other tasks display low inter-rater agreement too: music auto-tagging (Bigand & Aucouturier, 2013), music similarity and diversity (Flexer et al, 2021;Porcaro et al, 2022), automatic chord estimation (Koops et al, 2019), and beat tracking (Holzapfel et al, 2012). In short, MER has been openly criticized due to the subjectivity issue (Gómez-Cañónet al, 2021) -however we advocate for "embracing subjectivity and potentially leveraging the opportunities it offers for better learning" (Rizos & Schuller, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the proposed HC and MIX methods appear to significantly outperform the random baseline for SGD and XGB models. This finding leads us to promote the creation of subjectivity-aware machine learning methods which could have a high impact in novel applications of immersion in virtual reality (Warp et al, 2022) and emotion-based music recommendation (Grekow, 2021;Tarnowska, 2021)-several other tasks display low inter-rater agreement too: music auto-tagging (Bigand & Aucouturier, 2013), music similarity and diversity (Flexer et al, 2021;Porcaro et al, 2022), automatic chord estimation (Koops et al, 2019), and beat tracking (Holzapfel et al, 2012). In short, MER has been openly criticized due to the subjectivity issue (Gómez-Cañónet al, 2021) -however we advocate for "embracing subjectivity and potentially leveraging the opportunities it offers for better learning" (Rizos & Schuller, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the proposed HC and MIX methods appear to significantly outperform the random baseline for SGD and XGB models. This finding leads us to promote the creation of subjectivityaware machine learning methods -several other tasks have low inter-rater agreement too (music auto-tagging [65], music similarity and diversity [66,67], automatic chord estimation [68], and beat tracking [69]). In short, MER has been openly criticized due to the subjectivity issue [6] -however we advocate for "embracing subjectivity and potentially leveraging the opportunities it offers for better learning" [70].…”
Section: Discussionmentioning
confidence: 99%
“…While several works have addressed similarity perception, only a few have specifically addressed the diversity perception of lists. In the music domain (specifically, electronic music), for example, Porcaro et al (2022) found that instrument and samples, subgenre or sub-style, tempo, and mood strongly influence what track lists were considered diverse. On the artist level, the artists' origin and nationality, gender, and skin tone were considered key factors for diverse music lists.…”
Section: Assessing the Diversity Perception Of Item Listsmentioning
confidence: 99%
“…First, we addressed whether the familiarity of items influences the perception of a list. Similar to Porcaro et al (2022), where domain knowledge played a role in diversity perception, participants without background knowledge regarding a specific set of items might perceive the list differently (e.g., more diverse) than participants with more knowledge. Second, we addressed whether different diversity levels impacted the participants' decision processes, e.g., in terms of their perceived choice difficulty or choice confidence, cf.…”
Section: Fig 1 Overview Of the Studiesmentioning
confidence: 99%
See 1 more Smart Citation